PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (STUDI EMPIRIS PADA OPD KOTA PEKANBARU) - Sari, Puspita Ayunda; Wiguna, Melida; Afifah, Ulfa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to examine the effect of the effectiveness of internal control and compliance withaccounting rules on the tendency of accounting fraud in Regional Apparatus Organizations (OPD) inPekanbaru City. This research employs a quantitative approach using primary data collected throughquestionnaires distributed to 90 respondents from 30 OPDs. The data were analyzed using StructuralEquation Modeling –Partial Least Squares (SEM-PLS) with the SmartPLS 3.0 software. The resultsshow that the effectiveness of internal control has a significant negative effect on the tendency ofaccounting fraud. However, compliance with accounting rules does not have a significant effect. Thesefindings indicate that strengthening internal control systems is crucial in minimizing fraudulentpractices within local government institutions.Keywords: Internal Control, Compliance with Accounting Rules, Accounting Fraud, OPD, SEM-PLS.